104 Physiologic and Innate Immunity Responses of Beef Heifers Supplemented with an Immunomodulatory Feed Ingredient during a Lipopolysaccharide Challenge. (1st March 2018) - Brandao, A P; Cooke, R; Schubach, K M; Souza, K A; Schumaher, T F; da Silva, N S; Bohnert, D W; Marques, R
Abstract: This experiment compared physiological and innate immunity responses in healthy beef heifers receiving a lipopolysaccharide (LPS) challenge and supplemented (OMN ) or not (CON ) with an immunomodulatory feed ingredient (Omnigen-AF; Phibro Animal Health, Teaneck, NJ). Eight Angus × Hereford non-pregnant, non-lactating, 2-yr old heifers were ranked by BW (473 ± 8 kg; recorded for 3 consecutive days prior to experiment) and assigned to a 2 × 2 Latin square design containing 2 period of 35 d each (d 0 to 34). Heifers were housed in individual pens and had free-choice access to meadow foxtail ( Alopecurus pratensis L.) hay (59% TDN, 10.9% CP; DM basis), water and a commercial vitamin + mineral mix. Within each period, heifers received (as-fed basis) 227 g/d of dried distiller's grains (as-fed basis) including (OMN) or not (CON) 56 g of Omnigen-AF. On d 28 of each period (0800 h), heifers received an i.v. bolus dose (0.5 μg/kg of BW, diluted in 5 mL of 0.9% sterile saline) of bacterial LPS ( Escherichia coli 0111:B4). Heifer DMI was recorded daily from d 0 to 34. Heifer intravaginal temperature was recorded every 10 min from d 28 to 34. Blood was collected every 30 min from -1 to 4 h, and at 5, 6, 24, 48, 72, 96, 120 and 144 h relative to LPS administration. No treatment effects were detected ( P ≥ 0.29) for hay and total DMI. No treatment effects were detected ( P ≥ 0.35) for vaginal temperature and plasma concentrations of cortisol, insulin, haptoglobin, and tumor necrosis-α, as well as mRNA expression of chemokine ligand 5, cyclooxygenase 2, interleukin 8, and tumor necrosis-α . All these variables increased (time effect, P < 0.01) for OMN and CON heifers and peaked at 4.5, 4, 2.5, 48, 2.5, 0.5, 2, 2.5, and 1.5 h, respectively, after LPS administration. Yet, peak plasma haptoglobin was greater ( P < 0.01) in CON vs. OMN heifers (1.14 vs. 0.80 mg/mL, SEM = 0.07; respectively). Plasma glucose concentrations and mRNA expression of interleukin 8 receptor and L-selectin were also similar ( P ≥ 0.61) between OMN and CON heifers, and decreased (time effect, P < 0.01) for both treatments reaching nadir levels at 3.5, 1, and 2.5 h after LPS administration. Collectively, OMN supplementation did not have a substantial impact on physiological and innate immunity responses in healthy beef heifers receiving a LPS challenge.